Raman spectra of ionic liquids: a simulation study of AlF3 and its mixtures with NaF. - Akdeniz, Z; Madden, P (2006)
Theoretical Raman spectra of the melts of NaF/AlF3 mixtures have been obtained from computer simulations in order to examine how the Raman spectra reflect the coordination structure around the Al3+ ions. The Raman spectra, both polarized and depolarized, are calculated from a model for the dependence of the polarizability of the system on the ionic coordinates which was inspired by electronic structure calculations of the polarizabilities of ions in a condensed-phase environment. The shapes of the spectra and their evolution with composition in the mixtures conform remarkably well to those seen experimentally, and we discuss the relationship between the bands seen in the spectra and the vibrational modes of the AlFn(3-n) coordination complexes which are found in the melts. Finally, we calculate quantities which relate to the degree of cross-linking between these coordination complexes and their lifetimes.